DO DESENVOLVIMENTO COMO CRESCIMENTO ECONÔMICO AO DESENVOLVIMENTO COMO LIBERDADE: A EVOLUÇÃO DE UM CONCEITO - Dalvanir Avelino Silva (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2018)
The current perception of development, defended by the United Nations as a social and pluridimensional process, was constructed through the contribution of several schools of thought in the course of the historic and economic conjecture lived by the modern society. Starting from this perspective, this article proposes a reflection about the conception of development, constructed since the 20th Century, approaching its origins and meanings, as well as semantic shifts and the new questions drive the debate about the subject. It’s a theoretical article, using literature review as methodology, from which we conclude that fundamental changes related to the perception of development occurred throughout modern society and that the conception of development as freedom which currently pervades the debate is articulated with the development notion defended nowadays by national and international entities and institutions, constituting the theoretical basis guiding a set of public policies currently running.